A flow cytometeric approach to analyzing mature and progenitor endothelial cells following traumatic brain injury - Assis-Nascimento, Poincyane (J Neurosci Methods, 2016)
BACKGROUND: Traumatic brain injury (TBI) continues to be a major source of death and disability worldwide, and one of the earliest and most profound deficits comes from vascular damage and breakdown of the blood-brain barrier (BBB). Cerebral vascular endothelial cells (cvECs) and endothelial progenitor cells (EPCs) have been shown to play essential roles in vessel repair and BBB stability, although their individual contributions remain poorly defined. NEW METHOD: We employ TruCount beads with flow cytometry to precisely quantify cvECs, EPCs and peripheral leukocytes in the murine cortex after controlled cortical impact (CCI) injury. RESULTS: We found a significant reduction in the number of cvECs at 3 days post-injury (dpi), whereas the EPCs and invading peripheral leukocytes were significantly increased compared with sham controls. Proliferation studies demonstrate that both cvECs and EPCs are undergoing cell expansion in the first week post-injury. Furthermore, analysis of protein expression using mean fluorescent intensity found increases in PECAM-1, VEGFR-2, and VE-Cadherin expression per cell at 3 dpi, which is consistent with western blot analysis. COMPARISON WITH EXITING METHODS: Classic methods of cell analysis, such as histological cell counts, in the traumatic injured brain are labor intensive, time consuming, and potentially biased; whereas flow cytometry provides an efficient, non-biased approach to simultaneously quantify multiple cell types. However, conventional flow cytometry that employs capped events can provide misleading results in CNS injured tissues. CONCLUSIONS: We demonstrate that TruCount quantification using flow cytometry is a powerful tool for quantifying mature and progenitor endothelial cell changes after TBI.